Analysis of the Spanish Auditory Test of Speech in Noise (PAHRE) in a Population with Hearing Loss - Marlene Rodríguez-Ferreiro; Montserrat Durán-Bouza; Victoria Marrero-Aguiar (Audiology Research, 2024)
Background: Speech recognition in noise is one of the difficulties faced by people with hearing loss that increases with age. The recently developed Spanish Auditory Test of Speech in Noise (Prueba Auditiva de Habla en Ruido en Español, PAHRE) allows for the identification of these intelligibility difficulties in noise. The aim of this study was to assess speech recognition in noise in people with hearing loss and to test the benefits of the Lombard effect. Methods: The participants were 104 people with hearing difficulties, ranging in age from 37 to 98 years. The variables age, degree of hearing loss, presence of high-frequency dropout, and years of formal education were assessed. Results: Psychometric curves were obtained as a function of signal-to-noise ratio as well as threshold values of speech reception as a function of age group for mild and moderate hearing loss. The results indicated that the speech reception threshold increased with both age and the degree of hearing loss, becoming particularly significant after the age of 70. Furthermore, it was found that the combined factors of age, degree of hearing loss, and educational level predicted a high percentage of the variability in the speech reception threshold. Conclusions: Therefore, the Spanish Auditory Test of Speech in Noise could be a useful clinical tool for diagnosis, monitoring, auditory rehabilitation planning, and hearing aid fitting.